Development of Interactive Teaching Materials Based on Problem-Based Learning (PBL) in Indonesian Language Learning for Fifth Grade Elementary Students - Santi, Arfa Novia; Muhammadi, Muhammadi; Adrias, Adrias; Rayendra, Rayendra (Journal of Educational Sciences, 2026)
This study was conducted due to the limited use of interactive and technology-based teaching materials in Indonesian language learning at the elementary school level, which often relies on printed materials and results in low student engagement. The research aimed to develop Problem-Based Learning (PBL)-based interactive teaching materials to encourage active learning, provide immediate feedback, and support collaborative problem-solving for fifth-grade Indonesian language instruction. This research applied a research and development method using the ADDIE model, consisting of Analysis, Design, Development, Implementation, and Evaluation stages. The analysis stage involved observations and interviews with teachers and students from three elementary schools. The design and development stages focused on producing interactive multimedia-based teaching materials using Articulate Storyline 3. The product was then validated by experts to assess its content, language, and media feasibility. The validation results indicated that the teaching materials were categorized as very valid. Practicality testing showed average scores of 92.33% from teachers and 94.18% from students, both classified as very practical. Furthermore, the effectiveness test produced an N-Gain value of 0.8 (77.60%), indicating that the teaching materials were effective in improving student engagement and learning outcomes in Indonesian language learning.